2009
DOI: 10.1590/s0102-33062009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Diatomáceas epilíticas da subordem Sellaphorineae do rio do Monjolinho, São Carlos, SP, Brasil

Abstract: RESUMO -(Diatomáceas epilíticas da subordem Sellaphorineae do rio do Monjolinho, São Carlos, SP, Brasil). O presente trabalho é uma contribuição ao conhecimento da biodiversidade de diatomáceas epilíticas pertencentes à subordem Sellaphorineae do rio do Monjolinho, localizado no Município de São Carlos, São Paulo. O estudo taxonômico baseou-se na análise de 33 amostras coletadas no período de maio a outubro de 1998, em seis estações de coleta previamente estabelecidas. Foram identificados 31 táxons específicos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…However, the specimens observed in this study presented more linear outlines than the type specimens (Krammer 2000, figures 84: 13-15). The measures and outlines of the Lago dos Tigres material were also similar to that provided by Metzeltin et al (2005, figures 168:1-14), from Uruguay material, and to that found by Souza & Senna (2009), in São Paulo, including the slight undulation observed in the margins.…”
Section: Pinnularia Hudsoniisupporting
confidence: 85%
“…However, the specimens observed in this study presented more linear outlines than the type specimens (Krammer 2000, figures 84: 13-15). The measures and outlines of the Lago dos Tigres material were also similar to that provided by Metzeltin et al (2005, figures 168:1-14), from Uruguay material, and to that found by Souza & Senna (2009), in São Paulo, including the slight undulation observed in the margins.…”
Section: Pinnularia Hudsoniisupporting
confidence: 85%
“…The mean and standard deviations of counting efficiencies of diatom communities calculated according to Pappas and Stoermer (1996) on different substrates were as follows: vegetation, 82.5 ± 11.4%; sand, 86.1 ± 7.6%; stones, 83.6 ± 18.5%; silt/clay, 82.9 ± 14.2%; bricks, 76.4 ± 15.3% and glass, 78.0 ± 17.1%. The diatoms were identified to species level based on studies by Bourrelly (1981), Oliveira et al (2001), Souza (2002), Lobo et al, (2002Lobo et al, ( , 2004, Metzeltin et al, (2005), Bicudo and Menezes (2006), Salomoni et al (2006), Metzeltin and Lange-Bertalot (2007), Delgado et al (2007), Moura et al (2007), Soares et al (2007), Zalocar de Damitrovic et al (2007) and Souza and Senna (2009). In all cases, identification of diatom specimens was based on acid-cleaned specimens.…”
Section: Community Structurementioning
confidence: 99%
“…For southern Brazilian rivers, this species is cited as characteristic of α-polysaprobic pollution environments (very heavily polluted) (Lobo et al, 2002) and highly tolerant to eutrophication (Lobo et al 2004a(Lobo et al , 2010. Fallacia monoculata (Hustedt) D. G. Mann (Figures 44 to 53) Cosmopolitan species, extremely tolerant to eutrophication and organic pollution OuvirLer foneticamente (Van Dam et al, 1994;Souza and Senna, 2009;Lobo et al, 2004aLobo et al, , 2010Schuch et al, 2012). (Figures 18 to 26) Species found in freshwater (Lange-Bertalot, 2001) and brackish (Hodgson et al, 1997).…”
Section: Amphipleura Lindheimeri Grunow (Figures 2 To 4)mentioning
confidence: 99%
“…Despite the extensive hydrographic network that characterizes Brazil, divided into eight major basins (Amazon, Tocantins River, North Atlantic and Northeast, San Francisco River, eastern Atlantic, Parana River, Uruguay River and Southeast Atlantic), there are few systems of monitoring water quality that have been implemented (Moresco and Rodrigues, 2013), considering that they are essential to increase understanding of the problems related to pollution of aquatic ecosystems (Bodo, 1992;Mohlenberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%